Comparative Account of Floral Diversity of Four Major Islands (Bets) in Little Rann of Kachchh (LRK), Gujarat, India - Suthar, Ashok M.; Tatu, Ketan S.; Kamboj, R. D. (Indian Forester, 2019)
The present study compares floral diversity of four major islands (bets) in Little Rann of Kachchh (LRK) in Gujarat. During the study, transect and Daubenmire quadrat methods were used for collecting qualitative and quantitative data i.e. frequency and per cent cover of herbaceous plants. The study has revealed occurrence of 9 species of trees, 10 species of shrubs, 5 species of climbers, 21 species of herbs and 12 species of grasses. The study indicated more diversity of plant species on Jilandhar bet than that on Mardak bet, Nanda bet and Pung bet each. Aeluropus lagopoides (a grass) had higher per cent cover and frequency than those of other grass and herb species recorded in quadrats. The similarity and dissimilarity indices for plant species of the four bets of LRK were found to be 28 % and 72%, respectively.